2022
DOI: 10.3389/fphar.2022.908941
|View full text |Cite
|
Sign up to set email alerts
|

Herbal medicine for the treatment of chronic rhinosinusitis: A systematic review and meta-analysis

Abstract: Objectives: Chronic rhinosinusitis (CRS) is a disease with a high prevalence and a high socioeconomic burden. This study aimed to conduct a comprehensive systematic review to update the evidence on the use of herbal medicine (HM) for CRS treatment.Methods: A total of 14 electronic databases for randomized controlled trials (RCTs) evaluating the effects of HM on the treatment of CRS were searched for articles published before July 2021. The primary outcome was CRS severity post-treatment, measured with the Visu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
2
0
2

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 82 publications
(68 reference statements)
0
2
0
2
Order By: Relevance
“…In the experimental group, treatment was ineffective for 4 patients, potentially because of the presence of inflammation involving multiple paranasal sinuses in these patients, presenting a relatively wide scope of inflammation. For such patients, herbal medicine combined with conventional treatment may be more effective than herbal alone ( 18 ). The resolution of 2 cases in the placebo group may be related to taking dextromethorphan as needed.…”
Section: Discussionmentioning
confidence: 99%
“…In the experimental group, treatment was ineffective for 4 patients, potentially because of the presence of inflammation involving multiple paranasal sinuses in these patients, presenting a relatively wide scope of inflammation. For such patients, herbal medicine combined with conventional treatment may be more effective than herbal alone ( 18 ). The resolution of 2 cases in the placebo group may be related to taking dextromethorphan as needed.…”
Section: Discussionmentioning
confidence: 99%
“…Zur Wirksamkeit und Sicherheit von Phytotherapie existieren verschiedene systematische Reviews und Metaanalysen 4 5 6 7 8 . Im Folgenden wird ein Einblick in die internationale Forschungslandschaft gegeben und es werden exemplarisch Empfehlungen der EMA und medizinischer Leitlinien angeführt.…”
Section: Hintergrundunclassified
“…Die Nutzung von Phytotherapie zur Behandlung von akuten Atemwegsinfekten hat sich etabliert. Als Gegenstand von verschiedenen Metaanalysen, medizinischen Leitlinien und Arbeiten der EMA haben sich verschiedene Phytotherapeutika als eine sichere Behandlungsoption für Erkältungen und Husten sowohl bei Kindern als auch bei Erwachsenen erwiesen 5 6 7 17 . Die Ergebnisse bestätigen die traditionelle Anwendung von Pflanzenextrakten bei der Linderung von Symptomen und Steigerung des Wohlbefindens.…”
Section: Fazitunclassified
“…A systematic review of 34 studies of oral and/or nasal CHMs for acute or chronic rhinosinusitis, without surgery, found improvements in symptoms, sinus imaging and measures of mucociliary clearance [ 43 ]. Another systematic review that included 80 randomised controlled trials (RCTs) of herbal medicines for CRS, mostly from China, reported improvements associated with the herbal medicines, but that study combined studies of CRS without surgery and CRS post-surgery [ 45 ]. A review of 32 RCTs of CHMs following surgery reported benefits for combining CHM nasal irrigations with conventional medications [ 46 ].…”
Section: Introductionmentioning
confidence: 99%